1997
DOI: 10.2519/jospt.1997.26.5.244
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Behavior of Plantar Flexor Muscle-Tendon Unit at Rest

Abstract: A s most biological tissues, skeletal muscle and its tendon behave as viscoelastic materials in that they develop higher tension in response to increasing stretch velocity rates (1,6,32,33). This strain rate dependence in skeletal muscle is of nonreflex origin and likely related to a relaxation process defined as a decrease in muscle stiffness when it is stretched and maintained at a fixed length (l7,32). A low stretch velocity would allow more relaxation to take place, resulting in a lower resistance to passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 23 publications
4
31
1
4
Order By: Relevance
“…Torque was assigned a polarity consistent with the direction of the movement that it would generate (e.g., dorsiflexion torque was taken as positive). Each perturbation was made at a constant velocity of 5°/s so as to not evoke stretch reflex (Saripalli and Wilson 2005;Hufschmidt and Mauritz, 1985;Lamontagne et al 1997;Lorentzen et al 2010). The passive movement of the ankle occurred with nominal controller settings (robot torsional stiffness and damping) of 100 N·m/rad and 2 N·m·s/rad.…”
Section: Stiffness Measurementmentioning
confidence: 99%
See 4 more Smart Citations
“…Torque was assigned a polarity consistent with the direction of the movement that it would generate (e.g., dorsiflexion torque was taken as positive). Each perturbation was made at a constant velocity of 5°/s so as to not evoke stretch reflex (Saripalli and Wilson 2005;Hufschmidt and Mauritz, 1985;Lamontagne et al 1997;Lorentzen et al 2010). The passive movement of the ankle occurred with nominal controller settings (robot torsional stiffness and damping) of 100 N·m/rad and 2 N·m·s/rad.…”
Section: Stiffness Measurementmentioning
confidence: 99%
“…This affirms that our ankle position and torque data yielded a "near-true" estimate of passive ankle stiffness. 3) We also considered elicitation of stretch reflex: we used a slow-perturbation velocity to prevent evoking stretch-reflex activity (Saripalli and Wilson 2005;Lamontagne et al 1997;Lorentzen et al 2010). The decision to set 5°/s as the perturbation velocity in this protocol was, in part, based on previous work that has shown that stretch velocities of this magnitude do not evoke stretch reflex in both healthy (Saripalli and Wilson 2005;Lorentzen et al 2010) and stroke (Hufschmidt and Mauritz 1985;Lorentzen et al 2010) subjects under similar experimental conditions.…”
Section: Confounding Factorsmentioning
confidence: 99%
See 3 more Smart Citations